Contribution of Job Nature on Leadership Style among Academia - Milan Shrestha (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- Effective leadership practices in schools are only possible while headmaster and teachers adopt suitable leadership styles. The main purpose of this study is to identify the leadership styles as well as determine the association of democratic, autocratic and laissez-faire leadership style with each other among school teachers. Design/Methodology- This study is based on post-positivist research philosophy and cross-sectional survey as the research design which is confirmatory and explanatory in nature. It gathered the data via self-administer questionnaire from 345 school teachers and analyzed through descriptive statistics and parametric test. Findings- The researcher derived that school teachers adopted a more democratic leadership style and gave least prefer to the laissez-faire leadership style in schools. Meanwhile, the lacking of equal facility and access to power exercise contributes to making significant differences in leadership styles across the job nature of school teachers. Furthermore, this study assess that there is no relationship between autocratic, democratic and laissez-faire leadership styles. These distinct styles of leadership may develop the differences in work performances of school teachers. Practical Implications- This research provides the framework for another future researcher to investigate the input of job nature on leadership style among school teachers.